Modeling Affective Commitment and Job Satisfaction as A Mediating Role in Predicting Turnover Intention among Gen Z Employees - Cakti Indra Gunawan; Nanda Dwi Maharani; Dodi Wirawan Irawanto (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
This study investigated the impact of transformational leadership on Gen Z employees' intentions to leave their jobs. It used affective commitment and work satisfaction as mediating factors. The samples involved 300 Gen Z workers, aged 16 to 26, from various companies across five major Indonesian cities. This study employed a Likert scale questionnaire for data collection, and CFA and SmatPLS Version 22 were used for analysis. The findings demonstrated that transformational leadership significantly reduced the intention of turnover while also enhancing affective commitment and work satisfaction. Then, affective commitment had a strong negative influence on turnover intention. Contrary to job satisfaction, it had a substantial positive impact on turnover intention. Further analysis revealed that transformational leadership had a significant negative impact on turnover intention through affective commitment. Likewise, the influence of transformational leadership on turnover intention had a positive and significant impact if mediated by job satisfaction. An important contribution of this research found that contrary to general assumptions, especially for Gen Z employees, when transformational leadership is good and has a high level of job satisfaction, they will still have turnover intentions.